Polysaccharides as Potential Anti-tumor Biomacromolecules —A Review - Guo, Rui; Chen, Min; Ding, Yangyang; Yang, Pengyao; Wang, Mengjiao; Zhang, Haihui; He, Yuanqing; Ma, Haile (Frontiers in Nutrition, 2022)
Cancer, as one of the most life-threatening diseases, has attracted the attention of researchers to develop drugs with minimal side effects. The bioactive macromolecules, such as the polysaccharides, are considered the potential candidates against cancer due to their anti-tumor activities and non-toxic characteristics. The present review provides an overview on polysaccharides' extraction, isolation, purification, mechanisms for their anti-tumor activities, structure-activity relationships, absorption and metabolism of polysaccharides, and the applications of polysaccharides in anti-tumor therapy. Numerous research showed extraction methods of polysaccharides had a significant influence on their activities. Additionally, the anti-tumor activities of the polysaccharides are closely related to their structure, while molecular modification and high bioavailability may enhance the anti-tumor activity. Moreover, most of the polysaccharides exerted an anti-tumor activity mainly through the cell cycle arrest, anti-angiogenesis, apoptosis, and immunomodulation mechanisms. Also, recommendations were made to utilize the polysaccharides against cancer.